Surface Plasmon Resonance for Biosensing - Fantoni, Alessandro (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The rise of photonics technologies has driven an extremely fast evolution in biosensing applications. Such rapid progress has created a gap of understanding and insight capability in the general public about advanced sensing systems that have been made progressively available by these new technologies. Thus, there is currently a clear need for moving the meaning of some keywords, such as plasmonic, into the daily vocabulary of a general audience with a reasonable degree of education. The selection of the scientific works reported in this book is carefully balanced between reviews and research papers and has the purpose of presenting a set of applications and case studies sufficiently broad enough to enlighten the reader attention toward the great potential of plasmonic biosensing and the great impact that can be expected in the near future for supporting disease screening and stratification.